Hot electrons in beam-plasma discharge - Atamanov, V.M.; Biman, T.A.; Elizarov, L.I.; Ivanov, Al.A.; Pereslavtsev, A.V.; Shubin, N.N. (Вопросы атомной науки и техники, 2000)
The possibility to obtain hot electrons for the X-ray generation on the base of beam-plasma discharge in mirror magnetic trap is considered. One can obtain the hot electrons with the temperature 40 - 200 keV in beam plasma discharge in mirror magnetic trap. The experimental programme on the X-ray generation is carried out on the “Oratoria-10” installation. The view on the possible variant of the X-ray source based on beam-plasma discharge in mirror magnetic trap is given.